2020
DOI: 10.1177/0049475519874270
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric mucormycosis: tailoring surgical strategies to compliment antifungal chemotherapy. Different strokes for different folks

Abstract: Children manifesting soft-tissue fungal infections are uncommonly seen, more so the subgroup of invasive soft-tissue mucormycosis. Invasive fungal infections in various organs respond differently and are often complicated by an immune-compromised host. Repeated and aggressive clearance of disease till an infection-clear margin is obtained is the mainstay of surgical therapy. This is coupled with appropriate antifungal therapy and the management of any underlying medical conditions. From our experience, we prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Multiple surgeries may be required in the case of extensive disease. 11 Pana et al has demonstrated less mortality in patient given combined antifungals and surgery compared to those given antifungals alone (18.5% versus 60%). 17 Our patient required three sessions of complex operations, without which, it was clear that pharmaceutical interventions were not sufficient to control the infection.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Multiple surgeries may be required in the case of extensive disease. 11 Pana et al has demonstrated less mortality in patient given combined antifungals and surgery compared to those given antifungals alone (18.5% versus 60%). 17 Our patient required three sessions of complex operations, without which, it was clear that pharmaceutical interventions were not sufficient to control the infection.…”
Section: Discussionmentioning
confidence: 97%
“… 3 , 4 Histopathology and fungal culture are considered the gold standard for the diagnosis. 4 , 7 , 11 Mucorales are readily recognised morphologically on the basis of non-septate or occasionally pauci-septate, broad, thin walled hyphae with wide angled branching and evidence of angioinvasion. 3 , 9 , 11 We believe that the early diagnosis achieved within 24 hours of patient’s admission played a very important role in her satisfactory outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations